Frontispiece: Photoinitiated Thiol‐ene Reactions of Enoses: A Powerful Tool for Stereoselective Synthesis of Glycomimetics with Challenging Glycosidic Linkages. Issue 28 (15th May 2020) - Borbás, Anikó
Abstract : The photoinitiated, radical‐mediated thiol‐ene coupling reaction of unsaturated sugars is shown as a fast, simple and powerful new method for the stereoselective synthesis of a broad variety of thio‐linked glycomimetics. Addition of thiols to 2‐substituted hexoglycals under UV‐irradiation leads to exclusive formation of 1, 2‐ cis ‐α‐S‐glycosides independently of the sugar identity and the protecting groups applied. Application of exoglycals or 1‐substituted endoglycals as the alkene partners enables stereoselective formation of 2‐deoxy‐β‐glycosidic and β‐mannosidic structures. Hence, this method can be utilized for the efficient synthesis of stable carbohydrate mimetics, which would be very difficult by the classical ionic methods. For more information, see the Concept article by A. Borbás on page 6090 ff.